Functional Verification of Dynamically Reconfigurable FPGA-based Systems - Gong, Lingkan; Diessel, Oliver (Springer International Publishing : Imprint: Springer, 2015)
This book analyzes the challenges in verifying Dynamically Reconfigurable Systems (DRS) with respect to the user design and the physical implementation of such systems. The authors describe the use of a simulation-only layer to emulate the behavior of target FPGAs and accurately model the characteristic features of reconfiguration. Readers are enabled with this simulation-only layer to maintain verification productivity by abstracting away the physical details of the FPGA fabric.  Two implementations of the simulation-only layer are included: Extended ReChannel is a SystemC library that can be used to check DRS designs at a high level; ReSim is a library to support RTL simulation of a DRS reconfiguring both its logic and state. Through a number of case studies, the authors demonstrate how their approach integrates seamlessly with existing, mainstream DRS design flows and with well-established verification methodologies such as top-down modeling and coverage-driven verification. Provides researchers with an in-depth understanding of the challenges in verifying dynamically reconfigurable systems and the state-of-the-art methods used to overcome them; Guides engineers with systematic approaches and tools to achieve verification closure in their dynamically reconfigurable projects; Includes a comprehensive set of case studies, with an analysis of real bugs detected in the designs described; Uses tools and techniques compatible with mainstream products (e.g. Xilinx/Altera tools, ModelSim simulator, Verilog/VHDL design language, etc. ...).